Assessment of bowel preparation in patients undergoing colonoscopy - Gomes de Araújo, Gleice Kelly (2022)
Introduction: Colonoscopy has high diagnostic precision and the therapeutic possibility considered the gold standard ofchoice for the assessment, detection and treatment of lesions of the colon, rectum and ileum. It is used as an importantmethod of tracking colorectal cancer and diagnosing other intestinal diseases. For its performance, it is necessary toperform adequate intestinal preparation to allow a good visualization of the intestinal segments. Method: This is field research, descriptive with approach and quantitative analysis, carried out at the Proctology outpatient clinic of a tertiaryhospital in the Federal District. A total of 76 subjects participated in the study due to the drop in demand during the collection period. Results: Out of a total of 76 participants, 59 (77.6%) showed excellent preparation, 9 (11.8) with good preparation and 8 (10.5%) with regular preparation. The main indication was the screening for colorectal cancer. The symptoms most frequently mentioned during preparation were nausea in 26 (34.2%) and abdominal cramps in 18 (23.7%). Conclusion: Among exams performed, according to the Boston scale, 89.4% were classified as good and excellent, regular preparation at 10.5%.